Association between gain in adiposity and diabetic kidney disease worsening in type 2 diabetes is mediated by deteriorating glycaemic control: A 3-year follow-up analysis. (November 2019) - Moh, Angela Mei Chung; Wang, Jiexun; Tan, Clara; Ang, Su Fen; Ang, Keven; Subramaniam, Tavintharan; Sum, Chee Fang; Kwan, Pek Yee; Lee, Simon Biing Ming; Tang, Wern Ee; Lim, Su Chi
Abstract: Aims: Increased adiposity confers elevated risk for diabetic kidney disease (DKD) progression in type 2 diabetes mellitus (T2DM). This 3-year prospective study examined whether worsening of metabolic control e.g. development of uncontrolled diabetes mediated the relationship between increased adiposity and DKD deterioration. Methods: T2DM subjects who had adequately controlled diabetes (HbA1c < 8%) at initial recruitment were analysed (N = 853). HbA1c ≥ 8% at follow-up was classified as development of uncontrolled T2DM. Absolute changes in body weight (ΔWeight), body mass index (ΔBMI), and body fat mass (ΔBFM) were calculated by subtracting baseline from follow-up values. DKD deterioration (outcome) was defined as an increase in the composite ranking of relative risk by glomerular filtration rate and albuminuria levels (Kidney Disease: Improving Global Outcomes 2009). Results: Subjects with deteriorated DKD displayed lower reduction in body composition at follow-up than those who remained stable or/improved (all P < 0.05). In separate regression models, ΔWeight (risk ratio (RR):1.04, 95% CI:1.01–1.06), ΔBMI (RR:1.07, 95% CI:1.01–1.13), and ΔBFM (RR:1.03, 95% CI:1.01–1.06) were independently associated with worsened DKD. The associations were attenuated after accounting for the loss of glycaemic control. Binary mediation analysis revealed that the development of uncontrolled diabetes explained 41.7%, 45.4% and 39.7%, respectively, of the effects of ΔWeight, ΔBMI and ΔBFM on the outcome. Conclusions: Among T2DM individuals who had adequately-controlled T2DM at initial recruitment, the relationship between gain in adiposity and DKD deterioration is mediated by the development of poor glycaemic control over time. Therefore, preventing worsening adiposity and hyperglycaemia is pivotal to impede DKD progression.